Growth inhibition induced by antiprogestins RU-38486, ORG-31710, and CDB-2914 in ovarian cancer cells involves inhibition of cyclin dependent kinase 2 - Goyeneche, Alicia A. (Springer US, 2011)
Antiprogestins have been largely utilized in reproductive medicine, yet their repositioning for oncologic use is rapidly emerging. In this study we investigated the molecular mediators of the anti-ovarian cancer activity of the structurally related antiprogestins RU-38486, ORG-31710 and CDB-2914. We studied the responses of wt p53 OV2008 and p53 null SK-OV-3 cells to varying doses of RU-38486, ORG-31710 and CDB-2914. The steroids inhibited the growth of both cell lines with a potency of RU-38486 > ORG-31710 > CDB-2914, and were cytostatic at lower doses but lethal at higher concentrations. Antiprogestin-induced lethality associated with morphological features of apoptosis, hypodiploid DNA content, DNA fragmentation, and cleavage of executer caspase substrate PARP. Cell death ensued despite RU-38486 caused transient up-regulation of anti-apoptotic Bcl-2, ORG-31710 induced transient up-regulation of inhibitor of apoptosis XIAP, and CDB-2914 up-regulated both XIAP and Bcl-2. The antiprogestins induced accumulation of Cdk inhibitors p21(cip1) and p27(kip1) and increased association of p21(cip1) and p27(kip1) with Cdk-2. They also promoted nuclear localization of p21(cip1) and p27(kip1), reduced the nuclear abundances of Cdk-2 and cyclin E, and blocked the activity of Cdk-2 in both nucleus and cytoplasm. The cytotoxic potency of the antiprogestins correlated with the magnitude of the inhibition of Cdk-2 activity, ranging from G1 cell cycle arrest towards cell death. Our results suggest that, as a consequence of their cytostatic and lethal effects, antiprogestin steroids of well-known contraceptive properties emerge as attractive new agents to be repositioned for ovarian cancer therapeutics. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10637-011-9655-z) contains supplementary material, which is available to authorized users.